How Green Are Hotels in Ghana? Evidence From Star-Rated Hotels in Kumasi Metropolitan Area - sarkodie amoako, noble; Esi akyere Acquah, Hannah; Dery, Jane (ASEAN Journal on Hospitality and Tourism, 2024)
The study was conducted to assess green business practices among star-rated hotels in the Kumasi Metropolitan Area. This employed a survey and used a questionnaire to collect data from 60 managers from 84 licensed star-rating hotels.Data was analysed using both descriptive and inferential tests.The study results showed that star-rated hotels have implemented environmentally friendly practices, taking steps to reduce their water usage, adopting sustainable business practices for the long-term benefit of the environment, regular maintenance of sanitary facilities and pipes to prevent losses, and switching off the lights in unoccupied rooms. The study revealed that energy conservation, water conservation, eco-friendly cleaning, and water and energy monitoring were key green business policies adopted by star-rated hotels in the Kumasi Metropolitan Area. The study also showed that cost savings, customer demand, industry regulations and standards, environmental awareness, competitive advantage, and availability of resources were major factors that influenced the adoption of green practices by star-rated hotels in the Kumasi Metropolitan Area. The study suggests that the government shouldbe involved in all issues on the enforcement of green practices, as well as that employees' knowledge be raised consistently and their training be enhanced about the use of green practices.